Regulatory Medicine Against Financial Market Instability: What Helps And What Hurts? - Stefan Kerbl (Oesterreichische Nationalbank (OeNB), 2011)
Do we know if a short selling ban or a Tobin Tax result in more stable asset prices? Or do they in fact make things worse? Just like medicine regulatory measures in financial markets aim at improving an already complex system, cause side effects and interplay with other measures. In this paper an agent based stock market model is built that tries to find answers to the questions above. In a stepwise procedure regulatory measures are introduced and their implications on market liquidity and stability examined. Particularly, the effects of (i) a ban on short selling (ii) a mandatory risk limit, i.e. a Value-at-Risk limit, (iii) an introduction of a Tobin Tax, i.e. transaction tax on trading, and (iv) any arbitrary combination of the measures are observed and discussed. The model is set up to incorporate non-linear feedback effects of leverage and liquidity constraints leading to fire sales. In its unregulated version the model outcome is capable of reproducing stylised facts of asset returns like fat tails and clustered volatility. Introducing regulatory measures shows that only a mandatory risk limit is beneficial from every perspective, while a short selling ban – though reducing volatility – increases tail risk. The contrary holds true for a Tobin Tax: it reduces the occurrence of crashes but increases volatility. Furthermore, the interplay of measures is not negligible: measures block each other and a well chosen combination can mitigate unforeseen side effects. Concerning the Tobin Tax the findings indicate that an overdose can do severe harm.
Keywords: E37; G01; G12; G14; G18; 330; Tobin Tax; transaction tax; short selling ban; Value-at-Risk limits; risk management herding; agent based models